GROUNDS FOR IMPOSING SANCTIONS ON POLICE OFFICERS ACTING AS INTERMEDIARIES IN NARCOTICS SALES - Suci Pratiwi (Fakultas Hukum Universitas Sriwijaya, 2026)
Abstract: Narcotics are regulated in Law Number 35 of 2009 concerning Narcotics. Various kinds of narcotics crimes are often committed, such as narcotics abusers and dealers. In this research, narcotics crimes were committed by police officers whose position was law enforcement officers. The aim of this research is to explain and analyze what is the basis for imposing sanctions on police officers as intermediaries in the sale of narcotics. The research method that the author uses is Normative legal research. The results of the research are, the basis for imposing sanctions on Police Officers is by considering several things which include the juridical and non-juridical aspects of the defendant, the punishment is given to Police Officers with a weight added of 1/3 (one third) as stipulated in Article 52 of the Criminal Code, the application of the law will be carried out in the future based on Narcotics Law and Criminal Code as well as other regulations relating to Police Officers. The author's advice is: First, the judge in handing down must be more careful and thorough in considering all aspects. Second, Police Officers as law enforcement officers should be able to become advocates and good figures for the community.